The Influence of Modern Educational Management Practices on School Transformation - Shahzadi Hina Sain; Zohaib Hassan Sain; Aulia Luqman Aziz (Edu Spectrum: Journal of Multidimensional Education, 2024)
This research investigates the impact of modern educational management practices on school transformation in Pakistan. It explores how leadership and management practices in schools influence educational outcomes, particularly in the context of Pakistan's socio-political and cultural environment. The study identifies key practices such as transformational leadership, distributed leadership, and effective resource management as vital for driving positive change within schools. Additionally, it examines the challenges faced by school leaders in Pakistan, including resistance to change, lack of professional development opportunities, and socio-cultural factors that hinder the implementation of modern management practices. The research further discusses how school leadership can balance institutional goals with the individual needs of students and staff, ensuring a holistic approach to educational reform. Through a mixed-methods approach, including surveys and interviews with school leaders, the study highlights the importance of context-sensitive leadership and offers recommendations for overcoming the challenges in implementing modern management practices. The findings contribute to the broader understanding of how educational leadership can shape the future of schools in Pakistan, fostering a more dynamic and responsive education system.